Material removal characteristics of precorroded Lu2O3 laser crystals and elastic deformation model during nanoscratch process. (March 2020) - Zhang, Shuohua; Guo, Xiaoguang; Jin, Zhuji; Kang, Renke; Guo, Dongming
Abstract: At present, CMP is the only ultra-precision machining technology that can achieve global flattening. Unfortunately, CMP processing efficiency is extremely unsatisfactory. Although the processing efficiency can be improved by increasing the alkaline concentration of CMP slurry, the surface quality will deteriorate rapidly due to excessive concentration. In this study, the removal characteristics of both uncorroded and precorroded Lu2 O3 laser crystals were investigated based on nanoscratch tests with edge-forward Berkovich indenter. Further, the elastic deformation model considering both elastic extrusion and elastic recovery deformation was established. The origin of the microcracks was then discussed. The observed responses of surface quality were shown to depend greatly on the extent of elastic deformation prevalent during the nanoscratch and associated material removal processes. Highlights: The nanoscratch tests with Berkovich diamond indenter are conducted both on precorroded and uncorroded Lu2O3 laser crystals. Furthermore, by utilizing optical microscope, SEM and displacement transducers, elastic deformation model of materials in nanoscratch process are established. The following highlights can be drawn: (1) Material removal characteristics of precorroded Lu2O3 laser crystals were explored and determined for the first time. In addition, it is found that for precorroded crystals, microcracks are more likely to form along grooves during nanoscratch process. (2) The elastic deformation model considering both elastic extrusion and elastic recovery is established for the first time, and the causes of microcracks were analyzed from the point of stress and strain. (3) The obtained removal characteristics of precorroded Lu2O3 laser crystals can provide theoretical guidance for chemical mechanical polishing of hard and brittle materials. (4) The proposed elastic deformation model can be used as a powerful tool for evaluating the surface quality of nanoscratch.